Knowledge and attitude towards dementia among nursing students at Universiti Sains Malaysia - Sharif, Shara Syasya Athirah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Increasing number of people with dementia that have co-morbid medical disease, cognitive decline, and behavioral issues quite challenging and requires specific skills, attitudes, and knowledge regarding dementia. Nursing students are prepared to provide care for vulnerable persons, especially people with dementia. Nursing students tend to have a lower level of knowledge regarding dementia and attitude towards dementia than professional nurses. While there is little evidence that this problem has been explored in the context of Universiti Sains Malaysia nursing students. It will be important to find an element connected to knowledge and attitude among students that may be improved in the future. Thus, this study aimed to identify the knowledge and attitude towards dementia among nursing students in Universiti Sains Malaysia. This study was a quantitative study with a cross-sectional design. There were 140 nursing students at Universiti Sains Malaysia rescruited using stratified sampling method. Data were collected using the Dementia Knowledge Assessment Scale (DKAS) and Dementia Attitude Scale (DAS). Pearson Chi-square, One-way Anova, and Mann Whitney Unpaired were used for data analysis according to the type and distribution of the data. The mean score for knowledge on dementia was 18.77 (SD = 5.37), and the mean for attitude on dementia was 91.68 (SD = 17.51). The variables that were statistically significant correlated to knowledge of dementia was year of study only (F= 6.194, p <0.001). Meanwhile, the variables that were statistically significant correlated to attitude towards dementia were year of study (F= 3.976, p = 0.009) and family history of dementia (F= 4.883, p = 0.029). Hence, further studies to investigate the educational content related to the aging adult with dementia helps to indicate if it is sufficient for the students. Further study on students’ knowledge before and after learning on dementia to analyze the diference are also needed. This may show the importance of dementia education on students’ knowledge and attitude towards dementia. In addition, further research may compare universities with stand-alone curriculum and integrated curriculum for gerontology subjects. This may show the difference of nursing students’ knowledge and attitude among these two curricula.